Substrate Effects on the Electrical Properties in GaN-Based High Electron Mobility Transistors - Sung-Jae Chang (MDPI AG, 2021)
We report the electrical characteristics of GaN-based high electron mobility transistors (HEMTs) operated on various substrates/films. For the detailed investigation and comparison of the electrical properties of GaN-based HEMTs according to the substrates/films, GaN-based HEMTs were processed using 4-inch sapphire substrates and separated from their original substrates through the laser lift-off technique. The separated AlGaN/GaN films including processed GaN-based HEMTs were bonded to AlN substrate or plated with a 100 µm-thick Cu at the back-side of the devices since AlN substrate and Cu film exhibit higher thermal conductivity than the sapphire substrate. Compared to the sapphire substrate, DC and RF properties such as drain current, transconductance, cut-off frequency and maximum oscillation frequency were improved, when GaN-based HEMTs were operated on AlN substrate or Cu film. Our systematic study has revealed that the device property improvement results from the diminishment of the self-heating effect, increase in carrier mobility under the gated region, and amelioration of sheet resistance at the access region. C(V) and pulse-mode stress measurements have confirmed that the back-side processing for the device transfer from sapphire substrate onto AlN substrate or Cu film did not induce the critical defects close to the AlGaN/GaN hetero-interface.